EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) PADA MATA PELAJARAN IPA SISWA KELAS IV SD MUHAMMADIYAH 1 KEBOMAS GRESIK - Husnul Alfi Syahara; Nur Fauziyah; Ismail Marzuki (JUSEDA, 2020)
Husnul Alfi Syahara (NIM 14441013) Effectiveness of cooperative learning model type group investigation on science subjects fourth grade students Elementary School 1 of Muhammadiyah in Kebomas. Supervised by Nur Fauziyah, M.Pd and Ismail Marzuki, M.Pd.This study aims to describe the cooperative learning model group investigation on science subjects in the fourth grade IV Elementary School 1 of Muhammadiyah in Kebomas. This research is a descriptive research. The research subjects were 35 students. Data collection techniques used were observation and test results of learning by using research instruments in the form of observation sheets of student activities, teacher observation sheet in managing learning, and learning outcomes test sheets.The results of this study indicate that by using cooperative learning models the type of group investigation in science subjects is said to be effective. The activities of students during learning activities using cooperative learning models group investigation type are said to be active because in that category it reaches ≥ 50% which is equal to 81.15%. The ability of teachers to manage learning using the cooperative learning model type of investigation group is said to be effective because it reaches good criteria with a value of 80. The classical student learning outcomes have achieved classical completeness of 88.57%. Based on the results of this study it is recommended for elementary school teachers to apply the cooperative model group investigation type on science subjects.